Desarrollo jurídico sobre la Garantía de los Derechos de los hijos de crianza en Colombia. (2023)
The rights of Foster Children have been recognized by Colombian doctrine and jurisprudence, however, the legislator has not given sufficient guarantees for this subsidiary structure to enjoy equal rights as those children recognized by biological or adoptive ties. , as highlighted in judgment T-070 of 2015: "(...) pluralism and the evolution of human relations in Colombia, has as a consequence the formation of different types of families, different from those that are considered traditional, as was the biological family. Therefore, it is necessary for the law to adjust to legal realities, recognizing and providing protection to those family relationships where people are not united solely and exclusively by legal or natural ties, but by de facto situations, which arise by virtue of the ties of affection, solidarity, respect, protection and assistance.” (p. 2). It is for the above, that it is proposed in this scientific-legal research to analyze the legal development in Colombia regarding the guarantee of the rights of foster children, and to achieve this it is necessary to apply a methodology with a qualitative approach; whose purpose is to collect information from scientific literature, jurisprudence and national and international doctrines, to know how far this topic has advanced in the scientific-legal field, adding to the above; analysis of new jurisprudential lines, as well as a brief legal-comparative look between the United States and some Latin American countries. All the above, with the purpose of presenting, within a scientific-legal panorama, strategies that will contribute to the regulation of the rights of Foster Children in Colombia.